Pectinolytic enzyme production by Bacillus species and their potential application on juice extraction - Soares, MMCN; Da Silva, R.; Carmona, E. C.; Gomes, E. (Kluwer Academic Publ, 2001)
Five Bacillus strains isolated from decaying vegetable material were cultivated on wheat bran and endo-polygalacturonases, exo-polygalacturonase and pectin lyase activities in the crude enzymatic solution obtained were determined. Highest activity was observed for all enzymes when fermentation was carried out at 28 degreesC, the highest activity values were obtained after 120 h of cultivation for exo-PG and after 48 h for endo-PG and PL. The use of the enzymatic solution for treatment of fruits and vegetable mash afforded a high juice extraction and a pulp with good pressing characteristics.
Keywords: juice extraction; pectinases; pectin lyases; polygalacturonases